Frequency and Pattern of Injuries in Victims of Violence at District Sanghar - Rubina Salma Yasmin, Nadia Aslam, Ishtiaque Ali Langah, Shahla Imran, Azra Anwar, Pardeep Kumar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The main objective of the study was to determine the types and frequency of bodily medical and legal injuries that occur in a rural setting. Study Design: Retrospective study Place and Duration of Study: Civil Hospital Sanghar from 1st January 2020 to 31st December 2020 Methodology: One hundred cases were enrolled. Results: 90% of the cases were males and 10% were females. The frequency with which males were injured was higher than that of females. There were 45 cases of Shajjah, with 48 males and 9 females among the overall number. Conclusion: According to the findings of our study, the most common types of injuries were Shajjah and Jur-ghyr-e-jaiffa, which were followed by a variety of other types of injuries in the participants. Females were shown to be less susceptible to such injuries than males.